PS01.162: IS THERE A DIFFERENCE IN SURVIVAL BETWEEN YOUNGER AND OLDER GASTRIC CANCER (INCLUDING AEG II AND AEG III) PATIENTS AFTER GASTRECTOMY?. (14th September 2018) - Babic, Benjamin; Matthias Corvinus, Florian; Hadjijusufovic, Edin; Tagkalos, Evangelos; Lang, Hauke; Grimminger, Peter
Abstract: Background: The incidence of gastric cancer decreases in the western world, however, it remains one of the most common diseases (1). There is just little data from Europe comparing the outcome of young and elderly gastric cancer patients. This study compares, depending on the age of 266 patients, the outcome of 266 consecutive gastrectomy cases due to gastric cancer Methods: 266 consecutive patients with gastric cancer received a gastrectomy between 2008–2016 at our comprehensive cancer centre. The mean age of the patients in this study was 64 years old (21- 93 years). All patients were followed up regarding survival. The patients were separated in 6 different groups, depending on the age at the time of operation. The different groups were re-analysed and compared to each other regarding median and 5-year survival. Results: In this collective the 5-year survival rate for all patients was 43%. There were more diffuse type adenocarcinomas in Patients < 40 years. In younger patients the tumour was staged in an advanced stadium compared to the elderly patients group. There is a significantly higher 5-year survival rate for younger patients after gastrectomy. There is no significant difference, when separating patient groups in to decades of age. Conclusion: Young patients have a higher 5-year survival rate after gastrectomy compared to old patients. However, comparing patients from chronologic age in decades, the significance is not reproducible. Therefore gastrectomy or subtotal gastrectomy is the determining therapeutic approach for gastric cancer with an acceptable outcome in both young and elderly patients. Older patients might have an lower 5 year survival rate not only due to the cancer or the surgical therapy itself, it is related to comorbidities and a lower rate in neoadjuvant therapy as well Disclosure: All authors have declared no conflicts of interest.